Further biological, serological and biochemical characterization of North American, European and Southeast Asian strains of bovine herpesvirus 1 compared with other alphaherpesvirinae members - Trépanier, Pierre; Minocha, Harish C.; Ibrahim, Abdul L.; Sheikh-Omar, Abdul R.; Montpetit, Claude; Lecomte, Jacqueline; Alain, Robert; Lussier, Gilles; Trudel, Michael (Elsevier, 1988)
Hemagglutination activity, structural protein profiles and neutralization assays were used in a comparative study of bovine herpesvirus 1 strains from the U.S.A., Canada, Great Britain, Denmark and Malaysia with equine, feline and human herpesviruses in order to further characterize the bovine herpesvirus 1 hemagglutinin. Bovine herpesvirus 1 strains of different geographical origins all showed hemagglutinating activity for mouse erythrocytes; furthermore, feline herpesvirus 1 was also shown to hemagglutinate mouse erythrocytes. Analyses of partly purified viruses showed that a distinctive and specific polypeptides profile is associated with each species of herpesviruses used in our study; strains of bovine herpesvirus 1 from North America, Europe and Southeast Asia however, presented a remarkable similarity as to their electrophoretic protein patterns. A protein similar to the 97-kDa bovine viral hemagglutinin was not identified with the hemagglutinating feline herpesvirus. An important neutralization epitope on the bovine viral hemagglutinin was also not found on feline, equine and human herpesviruses but was identified on all bovine strains tested from North America, Europe and Southeast Asia stressing the importance of the bovine hemagglutinin for eventual prophylactic purposes.